The ACM Multimedia 2023 Computational Paralinguistics Challenge: Emotion Share & Requests - Schuller, Björn W.; Batliner, Anton; Amiriparian, Shahin; Barnhill, Alexander; Gerczuk, Maurice; Triantafyllopoulos, Andreas; Baird, Alice E.; Tzirakis, Panagiotis; Gagne, Chris; Cowen, Alan S.; Lackovic, Nikola; Caraty, Marie José; et al. (MM 2023 - Proceedings of the 31st ACM International Conference on Multimedia, 2023)
The ACM Multimedia 2023 Computational Paralinguistics Challenge addresses two different problems for the first time in a research competition under well-defined conditions: In the Emotion Share Sub-Challenge, a regression on speech has to be made; and in the Requests Sub-Challenges, requests and complaints need to be detected. We describe the Sub-Challenges, baseline feature extraction, and classifiers based on the 'usual' ComPaRE features, the auDeep toolkit, and deep feature extraction from pre-trained CNNs using the DeepSpectRum toolkit; in addition, wav2vec2 models are used.
CRIS-Team Scopus Importer:2023-12-22
Keywords: benchmark; challenge; complaints; computational paralinguistics; emotion share; requests